3D printing orientation controlled PMN-PT piezoelectric ceramics. Issue 6 (June 2023) - Zheng, Kun; Ding, Dafei; Quan, Yi; Zhuang, Jian; Fei, Chunlong; Zhao, Jinyan; Wang, Lingyan; Zhao, Tianlong; Wang, Zhe; Liu, Ming; Jiang, Zhuangde; Jiang, Zhishui; et al.
Abstract: Piezoelectric textured ceramics have drawn increasing research and industry interests by balancing the production cost and material performances. A new approach to realize the texture in piezoelectric ceramics is developed based on 3D printing stereolithography (SL) technique and successfully applied in the preparation of < 001 > -textured 0.71(Sm0.01 Pb0.985 )(Mg1/3 Nb2/3 )O3 -0.29(Sm0.01 Pb0.985 )TiO3 (1 %Sm-PMN-29PT) ceramics in this work. As a critical process in texture ceramic fabrication, the alignment of BaTiO3 templates along the horizontal direction is achieved by the shear force produced from the relative motion between the resin container and the blade during SL. The textured ceramics with obvious grain orientation features are successfully obtained. The enhanced piezoelectric properties of d 33 ≈ 652 pC N −1 and d 33 * ≈ 800 pm V −1 are achieved in the 3D printed textured ceramic, which are about 60 % and 40 %, respectively, higher than their non-textured counterparts. Moreover, the textured sample shows a significant improvement on thermal stability of d 33 *T, which varies by less than ± 6 % from RT to 110 °C. Furthermore, the introduction of 3D printing into the synthesis of textured piezoelectric ceramics shows great advantages over the traditional tape-casting method. This work is expected to provide a promising way for the future design of textured piezoelectric functional materials.